The Twilight of Structuralism in Linguistics? - Jędrzejko, Ewa (Forum Lingwistyczne, 2016)
The Twilight of Structuralism in Linguistics? This article attempts to offer a brief description of the overall situation in contemporary linguistics in the context of the changes taking place. Specifically, it refers to the ongoing discussions in the areias of various contemporary humanist disciplines on the subject of the achievements of structuralism and is future prospects in studies on language. The main theses considered here are: 1. One should not speak of the decline structuralism without indicating how this term should be understood and defining the scope of the teoretical-methodological principles developed by de various structuralist schools. 2. Taking into account the general principles and methods of the description, as given in the majority of contemporary literature on the subject it may reasonably be supposed that as yet no theoretical-methodological counter-proposal has emerged which, opposing structuralism, would discard al its basic premises while at the same time protecting the autonomy of linguistics as a science. The author endeavours to show that it would be more rational to speak of a successive – and broadly enriched – stage of evolution of the idea of structuralism. Key words: structuralism, linguistics, methodological principles, evolution of studies on language